Learning Organization Practices in Islamic Boarding Schools: Transforming Educational Culture and Institutional Performance - Taufik Ridwan; Agus Rohmat Hidayat; Amelia Amelia (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Pesantren is an Islamic educational institution that has existed for a long time; however, in the era of globalization, it must be able to transform in order to survive. Objective: To analyze the practice of learning organization in Pesantren X Islamic Boarding School, Cirebon, and the factors that support the development of organizational learning and its relationship to institutional performance. Method: The study adopted a qualitative case study methodology complemented by quantitative operationalization through the Learning Organization Index (LOI) based on Peter Senge’s five disciplines. Data collection was conducted through 24 semi-structured interviews, 38 observations (187.5 hours), and analyses of 47 institutional documents. Results: The LOI results indicated a score of 3.76 (75.2%), identifying the Pesantren as a developed learning organization. The dimension with the highest score was shared vision (81.7%), whereas the lowest was mental models (55.8%). The Aggregate Performance Index (API) value was 61.6%, with mental models identified as the primary area for improvement. The assessment was highly reliable, with an ICC value of 0.87. Conclusion: The findings from Pesantren X Islamic Boarding School demonstrate a high potential for becoming a learning organization, particularly in the aspects of shared vision and team learning. However, the institution continues to face significant challenges related to transformative mindsets concerning digitalization, gender, and sustainability. The theoretical contributions of this research are situated within the context of Islamic education, while the practical implications are directed toward reforming the management of Indonesian Islamic boarding schools.